Introduction to logic and critical thinking - Van Cleave, Matthew J.; BC Open Textbook Project; BCcampus ([publisher not identified], 2016)
"This is an introductory textbook in logic and critical thinking. The goal of the textbook is to provide the reader with a set of tools and skills that will enable them to identify and evaluate arguments. The book is intended for an introductory course that covers both formal and informal logic. As such, it is not a formal logic textbook, but is closer to what one would find marketed as a "critical thinking textbook""--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
Includes index.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online version; Title from PDF (viewed on June 14, 2017).
Keywords: Logic; Reasoning; Electronic books